The role of balneotherapy in helping older people take advantage of new job opportunities - Helmeczi (Magyar Gerontológia, 2025)
Maintaining and supporting the physical and mental health of older people is not only in the interest of individuals, but also of the community, as active and healthy older people are able to continue participating in the labor market, volunteering, and fulfilling family roles.